2004
DOI: 10.1159/000074925
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cell Therapy in the Treatment of Patients with Acute and Chronic Renal Failure

Abstract: Hemodialysis and hemofiltration have been important technologies in saving the lives of patients with acute (ARF) and chronic renal failure by clearing small solutes from plasma and thereby preventing death from acidemia, hyperkalemia, volume overload, and uremia. These therapeutic approaches, however, are still suboptimal, as patients with ARF have mortality rates exceeding 50%, and patients with end-stage renal disease (ESRD) have, on average, a life expectancy of 4–5 years. The preeminent cause of death in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 33 publications
(59 reference statements)
0
15
0
Order By: Relevance
“…For example, the extracorporeal renal tubule assist device utilizes a synthetic hemofilter connected in series with a bioreactor cartridge containing human proximal tubule cells (2). In addition, renal primordia obtained at a sufficiently early developmental stage have been demonstrated to undergo differentiation and grow when transplanted into animal hosts (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…For example, the extracorporeal renal tubule assist device utilizes a synthetic hemofilter connected in series with a bioreactor cartridge containing human proximal tubule cells (2). In addition, renal primordia obtained at a sufficiently early developmental stage have been demonstrated to undergo differentiation and grow when transplanted into animal hosts (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…It was reported that RAD is able to replace the functions of renal tubular epithelial cells [19][20][21] . ARF accompanied with MODS were treated with RAD constructed with rabbit primary proximal tubule epithelial cells, and the results showed that RAD was capable of reabsorbing Na + , glucose and para-aminohippuric acid, which could be inhibited respectively by ouabain (Na + -K + -ATPase inhibitor), phlorizin (glucose transport inhibitor) and probenecid.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that the pathogenesis of sepsis is not due to the dysfunction of a single protein but develops due to alterations in the complex interactions of a variety of cell components; it is unimaginable to expect supplying one therapeutic compound would have success. Therefore, a cell-based therapy may be a more successful strategy by providing a dynamic, interactive, and individualized therapeutic approach responding to the specific pathophysiological condition of the patient [11,19] .…”
Section: Discussionmentioning
confidence: 99%